INTENSITAS SERANGAN HAMA WERENG BATANG COKLAT (Nilaparvata lugens) TERHADAP TANAMAN PADI (Oryza sativa) DI DESA KEMBANGBILO KECAMATAN TUBAN KABUPATEN TUBAN: INTENSITAS SERANGAN HAMA WERENG BATANG COKLAT (Nilaparvata lugens) TERHADAP TANAMAN PADI (Oryza sativa) DI DESA KEMBANGBILO KECAMATAN TUBAN KABUPATEN TUBAN - SETIONO, TUTUS (Journal Science Innovation and Technology (SINTECH), 2024)
Rice is a food crop that is used as a staple food source and has a strategic and economic role in Indonesia. The availability of food production in this case the availability of rice is influenced by weather, climate, pests, and land. Based on data released by the Central Statistics Agency (BPS) in 2023, rice production in that year for population food consumption is estimated at around 30.90 million tons. This has decreased by 645.09 thousand tons or 2.05% compared to rice production in 2022 which was 31.54 million tons. The factor that makes the Kembangbilo Village area a rice farming area is because the plant can grow well on loose, fertile soil, contains a lot of organic matter, soil pH between 6-7 and sufficient groundwater content. Based on the results of observations in the field, the data obtained from the intensity of brown planthopper attacks in 5 sampling observations in the two Kembangbilo Hamlet and Lidan Hamlet. In the first observation aged 40 hst to the fifth aged 68 hst the results were the same, there was no brown planthopper pest attack. The factor that caused the absence of pest attacks was that the current weather was the dry season, therefore it did not support the breeding of brown planthopper pests, in addition, the simultaneous planting pattern reduced the occurrence of brown planthopper pest attacks, and farmers carried out good plant cultivation care, meaning always preventing pest attacks by spraying pesticides with a predetermined dose.